2001
DOI: 10.1007/s002130000553
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in the 5-HT 2C receptor (HT2RC) and the increase in slow wave sleep produced by olanzapine

Abstract: The 5-HT 2C receptor gene has been localised to the X chromosome and contains a C-G polymorphism at codon 23 (nucleotide 68) such that serine replaces cysteine in the receptor in about 15% of the population (Lappalainen et al. 1995;Sodhi et al. 1995). Sodhi et al (1995) found that patients with schizophrenia who possessed serine alleles of the 5-HT 2C receptor experienced a better therapeutic response to clozapine, an atypical antipsychotic agent which includes 5-HT 2C receptor antagonism among its pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…Both doses were associated with significant increases in SWS, sleep continuity, and subjective sleep quality. A second study by the same group comparing 5 mg of olanzapine with placebo confirmed the sleep changes observed before (22).…”
Section: Olanzapinesupporting
confidence: 72%
See 1 more Smart Citation
“…Both doses were associated with significant increases in SWS, sleep continuity, and subjective sleep quality. A second study by the same group comparing 5 mg of olanzapine with placebo confirmed the sleep changes observed before (22).…”
Section: Olanzapinesupporting
confidence: 72%
“…On the other hand, the difference could be unrelated to an antipsychotic effect and could be a direct impact of the atypical agents mediated through a distinct pharmacological property that is lacking in conventional neuroleptics. One argument against the extension of the antipsychotic effect hypothesis is that the antipsychotic impact of both conventional and atypical drugs takes several days if not weeks to become apparent, whereas improvements in sleep have been reported after single doses of olanzapine (21)(22)(23)(24). The impact on sleep is therefore more likely to be due to different pharmacological profiles between the conventional and atypical antipsychotics than simply associated with their antipsychotic effects.…”
Section: Discussionmentioning
confidence: 93%
“…Uncontrolled and placebo-controlled treatment studies using these medications as primary or adjunctive treatments demonstrate improved subjective sleep quality and reduced sleepiness in patients with schizophrenia, 178,179 unipolar depression, 180,181 and bipolar depression. [183][184][185][186][187] Similar self-reported and PSG effects have been demonstrated in small clinical studies of patients with depression, 188 mania, 189 and schizophrenia. [183][184][185][186][187] Similar self-reported and PSG effects have been demonstrated in small clinical studies of patients with depression, 188 mania, 189 and schizophrenia.…”
Section: Sedative Antipsychotic Drugssupporting
confidence: 68%
“…A large majority of these studies, regardless of treatment type, found that improving sleep continuity measures resulted in improvements in mood. Olanzapine has been shown to increase sleep continuity, subjective sleep measures and SWS in healthy volunteers [40-42] while an association between changes in sleep architecture and mood improvement in patients with MDD remains unclear [13]. Finally, Olanzapine has also been shown to improve cognition in schizophrenic patients [43]; however, its impact on cognition in depressive patients has not yet been fully described.…”
Section: Introductionmentioning
confidence: 99%